ENHANCING AESTHETIC JUDGMENT AND SOCIAL-CULTURAL COMPETENCE IN STUDENTS THROUGH ART EDUCATION - Esanova Lobar Kulmurotovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Abstract: This article explores methods for developing students’ aesthetic judgment and social-cultural competence through visual arts education. It highlights pedagogical strategies that integrate reflective analysis, interactive learning, and project-based activities. The study emphasizes the importance of combining cognitive, emotional, and aesthetic components to foster creative thinking, cultural awareness, and professional readiness in students.